A platinum-based Al2O3 / prototype and amorphous silica-alumina catalyst with tunable Brønsted acid, its preparation method and application
Patent Information
- Application Number
- CN202611262166.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-20
AI Technical Summary
[0009]本发明的目的中是为了解决金属-酸双功能的加氢裂化催化剂的孔道结构与酸性质难以协同的问题而提供一种B酸可调的铂基Al2O3/雏晶和无定形硅铝催化剂及其制备方法和应用
1)本发明通过使用沸石雏晶的最高短程有序且长程无序,超小晶粒尺寸、超短孔道以及较大的外表面积的特点,减少扩散阻力、大分子反应物更容易接近活性位点,有效克服大分子芳烃的传质限制,抑制了二次反应而防止催化剂快速积碳失活。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrocracking catalysis technology, and relates to a platinum-based Al2O3 / proto-crystal and amorphous silica-alumina catalyst with tunable Brønsted acid, its preparation method and application. Background Technology
[0002] Despite increasing efforts to develop renewable energy, the trend towards heavier crude oil is leading to a significant increase in polycyclic aromatic hydrocarbons (PAHs) in low-quality diesel fractions, such as catalytic cracking light cycle oil, reaching 40-60% by mass. PAHs are structurally stable and difficult to degrade, resulting not only in reduced diesel cetane number and poor combustion performance but also serious environmental problems. Therefore, efficient conversion of PAHs is essential to improve crude oil resource utilization and reduce pollutant emissions. Hydrocracking technology is considered one of the most promising technical routes for converting PAHs in low-quality diesel fractions. Hydrocracking can efficiently convert PAHs into high-value-added monocyclic aromatic hydrocarbons (BTX, i.e., benzene, toluene, and xylene), which is crucial for improving refining economics and reducing dependence on imported aromatics. The hydrocracking process is a complex series of reactions involving hydrogenation saturation, ring-opening cracking, isomerization, and alkyl transfer, placing high demands on the multifunctional synergy of catalysts.
[0003] Traditional bifunctional hydrocracking catalysts typically consist of a metal active component and an acidic component. The metal component provides hydrogenation / dehydrogenation functions, while the acidic component is responsible for reactions such as cracking and isomerization. However, while commonly used supports like Al₂O₃ possess good mechanical strength and a regular pore structure, they have few strongly Brønsted acid sites, making it difficult for large aromatic molecules to undergo cracking reactions. Amorphous silica-alumina, although tunable in acidity, faces bottlenecks due to disordered pores and poor structural stability. Traditional zeolite supports, with their narrow micropores, result in high diffusion resistance, making it difficult for large reactants to access active sites, easily triggering secondary reactions and leading to rapid carbon deposition and deactivation of the catalyst. With the increasing weight of feedstocks and increasingly stringent environmental regulations, traditional hydrocracking catalysts can no longer meet current industrial production demands. Therefore, developing and designing novel acidic components to regulate pore structure and acid properties, achieving highly efficient synergy between metal and acid functions, has become a major research direction for improving the performance of hydrocracking catalysts.
[0004] Hydrocracking is a crucial technology in petroleum processing for converting heavy fractions into light, clean fuels and chemical feedstocks. Hydrocracking catalysts are bifunctional metal-acid catalysts, typically composed of a hydrogenation-active metal component and an acidic support. The acidity and pore structure of the catalyst directly affect its cracking activity, product selectivity, and lifetime. Therefore, how to improve the overall performance of hydrocracking catalysts by controlling their pore structure and acidity has always been a research hotspot and challenge in this field.
[0005] Chinese patent CN119186544A discloses an amorphous silica-alumina containing moderately strong Brønsted acid, its preparation method, and its application. The method involves mixing an aluminum source, a silicon source, an inorganic alkali, a template agent, and water in a specific molar ratio to obtain a precursor solution. This solution is then subjected to aging, crystallization, solid-liquid separation, drying, and calcination to obtain a sodium-type ASA sample. Following ammonia exchange treatment, the sample is further separated, dried, and calcined to obtain an amorphous silica-alumina support containing moderately strong Brønsted acid. This support is composed of molecular sieve secondary structural units. At 200°C, the Brønsted acid content accounts for 40–55% of the total infrared acid content, with the outer surface accounting for 10–45% and the micropores containing 1–40%. This supported metal was used as a hydrocracking catalyst, exhibiting good reactivity and diesel yield in the hydrocracking reaction of FTS wax.
[0006] The hydrocracking catalyst disclosed in patent CN119186544A has two main shortcomings: 1) Its amorphous silica-alumina carrier requires the preparation of a sodium-type intermediate and then ammonia exchange treatment to obtain Brønsted acid sites. The preparation process takes several days, is complicated and has a long cycle, puts great pressure on waste disposal, is environmentally unfriendly and is not conducive to continuous industrial production.
[0007] 2) The active metal in the catalyst is simply loaded onto the sodium-type ASA sample, making it difficult to achieve uniform loading of the active metal. This may lead to a reduction in the stacking of the metal active components and the catalytic contact area, resulting in a decrease in catalytic efficiency.
[0008] Therefore, there is an urgent need to develop a catalyst for the hydrocracking of polycyclic aromatic hydrocarbons to address the challenge of synergistic effects between the pore structure and acid properties of existing hydrocracking catalysts. Solving this problem is expected to improve the metal-acid bifunctionality of hydrocracking catalysts, thereby further enhancing their catalytic activity. Summary of the Invention
[0009] The purpose of this invention is to address the challenge of achieving synergistic pore structure and acid properties in metal-acid bifunctional hydrocracking catalysts by providing a platinum-based Al₂O₃ / prototype and amorphous silica-alumina catalyst with tunable Brønsted acid (B-acid) properties, along with its preparation method and applications. This invention successfully constructs a metal-acid synergistically regulated bifunctional catalyst by loading platinum onto a composite support composed of Al₂O₃, zeolite prototypes, and amorphous silica-alumina. The zeolite prototypes possess ultra-small crystal size (less than 10 nm), ultra-short pores, and a large external surface area, effectively overcoming the mass transfer limitations of large aromatic molecules and providing tunable B-acid sites. The Al₂O₃ support facilitates the uniform dispersion of platinum metal, while the amorphous silica-alumina contains both B-acid and Lewis acid centers. Based on these structural advantages, the synergistic combination of these materials allows the catalyst to achieve uniform loading of the active metal component and synergistic pore structure and acid properties in the metal-acid bifunctional hydrocracking catalyst, improving the overall performance of the catalyst for hydrocracking and exhibiting excellent catalytic activity for the hydrocracking of polycyclic aromatic hydrocarbons such as naphthalene and tetrahydronaphthalene.
[0010] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a platinum-based Al2O3 / prototype and amorphous silica-alumina catalyst with tunable Brønsted acid, comprising a composite support composed of Al2O3, zeolite prototype and amorphous silica-alumina, and platinum supported on the composite support.
[0011] Furthermore, the platinum loading is 0.01~0.1wt%.
[0012] Furthermore, the platinum loading is preferably 0.05 wt%.
[0013] Furthermore, the zeolite precursor crystals have a particle size of 6-15 nm; the platinum loaded on the composite support is uniformly distributed; the zeolite precursor crystals have stacked mesopores with a pore size of 4-8 nm.
[0014] Furthermore, the preferred particle size of the zeolite primordia is 8-10 nm; Furthermore, the pore size of the mesoporous structure is preferably 4~6 nm.
[0015] This invention also provides a method for preparing platinum-based Al2O3 / prototype and amorphous silica-alumina catalysts with tunable Brønsted acid, comprising the following steps: S1. Mix silicon source and aluminum source, perform first aging, add template agent, perform second aging, and then perform microwave hydrothermal treatment to obtain zeolite crystalline liquid containing amorphous silicon and aluminum. S2. Zeolite precursor containing amorphous silicon and aluminum is impregnated onto Al2O3 to obtain a composite carrier precursor; S3. Prepare a platinum precursor dispersion, and load the prepared platinum precursor dispersion onto the composite support precursor to obtain the catalyst precursor. S4. The catalyst precursor is heat-treated and then reduced to obtain platinum-based Al2O3 / zeolite precursors and amorphous silica-alumina catalysts with tunable Brønsted acid.
[0016] Furthermore, step S1 includes one or more of the following: a. The aluminum source includes one or more of aluminum isopropoxide, aluminum nitrate, and aluminum chloride; b. The silicon source includes one or more of tetraethyl orthosilicate, water glass, and silica sol; c. Template agents include tetrapropylammonium hydroxide; d. The actual silicon-to-aluminum ratio of the obtained zeolite rudiments is greater than or equal to 30; e. The molar ratio of silicon to template agent in the silicon source is 1:(0.5~0.8); the first aging time is 8~16h, and the temperature is room temperature; the second aging time is 20~36h, and the temperature includes room temperature; f. The microwave hydrothermal treatment includes sequential low-temperature hydrothermal treatment and high-temperature hydrothermal treatment; The low-temperature hydrothermal treatment is performed at a temperature of 50~100℃ for a time of 70~120min; The high-temperature hydrothermal treatment is performed at a temperature of 120~150℃ for a time of 40~80 minutes.
[0017] Further, in step S1, the molar ratio of silicon to aluminum in the silicon source is greater than or equal to 60; Furthermore, in step S1, the molar ratio of silicon to aluminum in the silicon source is 60 to 200.
[0018] Furthermore, in step S1, the molar ratio of silicon to template agent in the silicon source is preferably 1:(0.6~0.7). Furthermore, in step S1, the molar ratio of silicon to template agent in the silicon source is preferably 1:0.617.
[0019] Furthermore, in step S1, the first aging time is preferably 10-12 hours; the second aging time is preferably 24-30 hours. Furthermore, in step S1, the microwave hydrothermal treatment includes sequential low-temperature hydrothermal treatment and high-temperature hydrothermal treatment; The preferred temperature for the low-temperature hydrothermal treatment is 70~90℃, and the preferred time is 80~100min; The preferred temperature for the high-temperature hydrothermal treatment is 130~140℃, and the preferred time is 50~70min; Furthermore, the microwave hydrothermal treatment employs a microwave synthesis reactor; Furthermore, the microwave synthesis reactor has a power of 150~250W; Further, in step S2, the mass ratio of Al2O3 to zeolite precursor liquid is 0.2:1 to 0.5:1; Al2O3 includes γ-Al2O3; Furthermore, depending on the different acidic support, the mass ratio of Al2O3 to zeolite precursor solution is 0.2:1 to 0.5:1 (this ratio is SC to Al2O3), where the ratio of SC to ASA is 7:3. Furthermore, the composite carrier precursor is dried to constant weight in air at a temperature of 60~120℃ before proceeding to the next step of processing.
[0020] Furthermore, the composite carrier precursor must be dried to constant weight in air before proceeding to the next step of processing, preferably at a temperature of 80~100℃; Furthermore, the platinum precursor dispersion in step S3 includes a water-soluble platinum salt; the catalyst precursor is dried to constant weight in air at a temperature of 60~120℃ before proceeding to the next step of processing.
[0021] Furthermore, the catalyst precursor is dried to constant weight in air before proceeding to the next step of processing, preferably at a temperature of 80-100°C.
[0022] Further, in step S4, the heat treatment includes calcination, the calcination atmosphere is air, the temperature is 300~800℃, preferably 300~700℃, more preferably 400~500℃; the calcination time is 2~8h, preferably 3~7h, more preferably 4~6h; Further, in step S4, the atmosphere for the reduction treatment is hydrogen, the temperature is 200~600℃, preferably 300~500℃, and the reduction time is preferably 2~8h, more preferably 4~6h.
[0023] Furthermore, before the heat treatment, a pre-reduction is performed in a hydrogen atmosphere at a temperature of 200-500°C, preferably 300-400°C, for a pre-reduction time of 4-8 hours, preferably 5-7 hours.
[0024] The present invention also provides the application of the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and amorphous silica-alumina catalyst described above in hydrocracking.
[0025] In this invention, the hydrocracking includes the hydrocracking of polycyclic aromatic hydrocarbons. Preferably, the polycyclic aromatic hydrocarbons include one or more of naphthalene, anthracene, and phenanthrene, and more preferably naphthalene.
[0026] In this invention, the application method of the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and amorphous silica-alumina catalyst includes the following steps: mixing the substrate, organic solvent, and Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and amorphous silica-alumina catalyst, and carrying out a hydrocracking reaction under a hydrogen atmosphere.
[0027] Furthermore, the mass ratio of the substrate to the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and the amorphous silica-alumina catalyst is (2~5):1; Furthermore, the preferred mass ratio of the substrate to the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and the amorphous silica-alumina catalyst is (3~4):1.
[0028] Furthermore, the organic solvent preferably includes one or more of n-octane, n-decane, and hexadecane; Furthermore, the mass ratio of the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and amorphous silica-alumina catalyst to the volume ratio of the organic solvent is 1 g:(200~500) mL. Furthermore, the preferred mass ratio of the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor and amorphous silica-alumina catalyst to the volume of the organic solvent is 1 g:(300~400) mL.
[0029] In this invention, mixing includes stirring at a speed of 400-600 r / min. The initial pressure of the hydrogen gas is 1-5 MPa.
[0030] Furthermore, the stirring speed is preferably 500 r / min, and the initial pressure of the hydrogen gas is 2~4 MPa. Furthermore, the initial pressure of the hydrogen gas is more preferably 3 MPa.
[0031] Furthermore, the temperature of the hydrocracking reaction is 150~400℃; Furthermore, the preferred temperature for the hydrocracking reaction is 200~350℃; Furthermore, the preferred temperature for the hydrocracking reaction is 350°C; Furthermore, the heating rate from room temperature to the temperature of the hydrocracking reaction is 6~10℃ / min; Furthermore, the preferred heating rate for raising the temperature from room temperature to the temperature of the hydrocracking reaction is 8°C / min; Furthermore, the timing begins when the temperature reaches the temperature of the hydrocracking reaction, and the time for the hydrocracking reaction is 2-6 hours. Furthermore, the hydrocracking reaction time is preferably 3-5 hours; Furthermore, the hydrocracking reaction is preferably carried out over a period of 4 hours.
[0032] Furthermore, the hydrocracking reaction is preferably carried out in a batch reactor, and the reactor is preferably sealed before use and then high-purity hydrogen is introduced to replace the air inside the reactor. Furthermore, the reactor is preferably a Laibei high-pressure reactor.
[0033] Furthermore, after the hydrocracking reaction, the present invention preferably includes a post-treatment, which includes cooling the reaction solution of the hydrocracking reaction to room temperature.
[0034] The present invention does not have any particular limitation on the cooling method, and any cooling method well known in the art can be used, such as natural cooling.
[0035] The present invention does not have any particular limitation on the mixing method, as long as the raw materials are mixed evenly, such as stirring.
[0036] The present invention does not have any special limitations on the speed and time of stirring and mixing, as long as the raw materials are mixed evenly.
[0037] This invention uses common silicon sources, tetrapropylammonium hydroxide, aluminum sources, and water-soluble platinum salts as raw materials to prepare platinum-based Al2O3 / zeolite precursors and amorphous silicon-aluminum catalysts with tunable Brønsted acid. The raw materials are widely available, inexpensive, and have low production costs.
[0038] Compared with the prior art, the present invention has the following advantages: 1) By using the characteristics of zeolite rudimentary crystals with the highest short-range order and long-range disorder, ultra-small crystal size, ultra-short channels and large external surface area, the present invention reduces diffusion resistance, makes it easier for large molecular reactants to access active sites, effectively overcomes the mass transfer limitation of large molecular aromatics, inhibits secondary reactions and prevents rapid carbon deposition and deactivation of catalysts.
[0039] 2) This invention uses an Al2O3 carrier, microwave hydrothermal treatment and reduction treatment to uniformly disperse platinum metal. The amorphous silicon aluminum contains both Brønsted acid and Lewis acid centers, increasing the number of acid sites and effectively promoting the cracking reaction of macromolecular aromatic hydrocarbons.
[0040] 3) This invention successfully constructed a bifunctional catalyst with synergistic metal-acid function by supporting platinum on a composite support composed of Al2O3, zeolite precursors, and amorphous silica-alumina. This catalyst enhances the overall performance of hydrocracking catalysts by controlling the synergistic effect of the catalyst's pore structure and acid properties, exhibiting excellent catalytic activity in the hydrocracking of naphthalene, tetrahydronaphthalene, and other polycyclic aromatic hydrocarbons. The platinum-based Al2O3 / zeolite precursor and amorphous silica-alumina catalyst with tunable B-acid provided by this invention was applied to the hydrocracking of naphthalene. At 350°C and 3 MPa hydrogen pressure for 4 hours, the conversion rate of naphthalene reached 99%, and the BTX selectivity exceeded 10%. Further application to the hydrocracking of tetrahydronaphthalene resulted in a BTX selectivity of 30%.
[0041] 4) The preparation method provided by this invention uses commercially available common chemicals as raw materials, such as tetraethyl orthosilicate, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraammineplatinum nitrate, which are widely available and inexpensive. The preparation process only involves conventional operations such as mixing, aging, crystallization, loading, drying, calcination, and reduction. No complex equipment is required. There is no special atmosphere except for the reducing atmosphere. The maximum processing temperature does not exceed 800°C throughout the process. The operating conditions are mild and conducive to industrial-scale production. Attached Figure Description
[0042] Figure 1 XRD patterns of the catalysts prepared in Example 1 and Comparative Examples 1-4; Figure 2 The N2 adsorption-desorption curves are shown for the catalysts prepared in Example 1 and Comparative Examples 1-4. Figure 3 The pore size distribution diagram is for the catalyst prepared in Comparative Example 1. Figure 4 Pore size distribution diagram of the catalyst prepared in Example 1 Figure 5 TEM images of the catalysts prepared in Example 1 and Comparative Example 1; Figure 6 TEM images of the catalysts prepared in comparative examples 2-4; Figure 7 The NH3-TPD diagrams are for the catalysts prepared in Example 1 and Comparative Examples 1-4. Figure 8 The Py-IR spectra of the catalysts prepared in Example 1 and Comparative Examples 1-4 are shown below. Figure 9 The graph shows a comparison of the conversion rate and BTX selectivity of the catalysts prepared in Example 1 and Comparative Examples 1-4 in the naphthalene hydrocracking reaction. Figure 10 The graph shows a comparison of the conversion rate and BTX selectivity of the catalysts prepared in Example 1 and Comparative Examples 1-4 in the tetrahydronaphthalene hydrocracking reaction. Figure 11A comparison of the conversion rate and BTX selectivity of the catalysts prepared in Comparative Example 1 and Preferred Examples 1-3 in the tetrahydronaphthalene hydrocracking reaction; Figure 12 The graph shows a comparison of the conversion rate and BTX selectivity of the catalysts prepared in Examples 1 and 2-4 in the tetrahydronaphthalene hydrocracking reaction. Figure 13 A comparison of the conversion rate and BTX selectivity of the catalysts prepared in Comparative Examples 2 and Preferred Examples 4-6 in the tetrahydronaphthalene hydrocracking reaction; Figure 14 A comparison of the conversion rate and BTX selectivity of the catalysts prepared in Comparative Examples 3 and Preferred Examples 7-9 in the tetrahydronaphthalene hydrocracking reaction; Figure 15 The particle size distribution of the zeolite precursor crystals prepared in Example 1 is shown. Detailed Implementation
[0043] The present invention will now be described in detail with reference to specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention includes, but is not limited to, the following embodiments.
[0044] In the examples described below, unless otherwise specified, the reagents used are commercially available products and the methods used are those known in the art.
[0045] Example 1: (1) Aluminum ions and silicon atoms were mixed in a molar ratio of 1:60 with tetraethyl orthosilicate (silicon source) and aged for 16 h at room temperature. Then, a template agent, tetrapropylammonium hydroxide aqueous solution (75% concentration), was added to the mixture and aged for 24 h at room temperature. The mixture was then subjected to microwave hydrothermal treatment in a hydrothermal synthesizer, followed by low-temperature hydrothermal treatment at 90 °C for 90 min, and then high-temperature hydrothermal treatment at 140 °C for 70 min to obtain a zeolite precursor liquid containing amorphous silicon and aluminum. The molar ratio of silicon to tetrapropylammonium hydroxide in the tetraethyl orthosilicate was 1:0.617. The actual silicon-to-aluminum ratio of the obtained zeolite precursor was Si:Al = 30, measured by ICP. Figure 15 It can be seen that the particle size of the zeolite precursor crystals was measured by DLS nanoparticle size analysis, and the precursor crystal particle size was 8~10nm; the ratio of zeolite precursor crystals SC to Al2O3 was adjusted to 0.2:1 (mass ratio), and the ratio of SC to amorphous aluminum silicate (ASA) was 7:3.
[0046] (2) After determining the solid content of the zeolite precursor solution containing amorphous silica and aluminum, the zeolite precursor solution containing amorphous silica and aluminum is immersed in Al2O3 according to the solid content to obtain the composite carrier precursor. Before proceeding to the next step of processing, the composite carrier precursor should be dried to constant weight in air atmosphere, preferably at a temperature of 80~100℃. The method for testing the solid content is to take about 2g of the dialyzed zeolite precursor solution (m1) into a 5ml centrifuge tube, place it in an 80℃ oven for 36h to ensure that the precursor solution is completely dried and only solid precursor crystals remain, and measure the mass of the solid precursor crystals (m2). The solid content is X=m2 / m1. Therefore, the total amount of precursor crystal solids in the precursor solution after microwave hydrothermal treatment can be calculated by the solid content.
[0047] (3) The prepared tetraammine nitrate platinum dispersion (platinum loading 0.05wt%) was loaded onto the composite carrier precursor and dried in an oven at 80°C to constant weight.
[0048] (4) The catalyst is calcined at 500℃ for 6 hours and then further hydrogenated at 500℃ for 6 hours to obtain a catalyst called Pt / Al2O3-SC-ASA, wherein the mass ratio of SC to Al2O3 is 0.2:1, that is, the mass of component SC is 20% of the mass of component Al2O3.
[0049] Comparative Example 1: The Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor catalyst was prepared according to the method of Example 1, the difference being that: In step (1), the zeolite precursor solution containing amorphous silica and aluminum is placed in a cellulose semipermeable membrane, immersed in water, and dialyzed at room temperature for 24 hours. The deionized water is then replaced every 12 hours thereafter. The dialysis is continued until the liquid outside the dialysis bag is neutral to obtain the dialyzed zeolite precursor solution.
[0050] In step (2), the solid content of the dialysis zeolite crystal solution is measured and then mixed with Al2O3 to adjust the ratio of SC to Al2O3 to 0.2:1 (mass ratio). Without introducing amorphous silicon and aluminum, the rest of the operation is the same, and the resulting catalyst is denoted as Pt / Al2O3-SC, where the mass ratio of SC to Al2O3 is 0.2:1, that is, the mass of component SC is 20% of the mass of component Al2O3.
[0051] Comparative Example 2: Prepared according to the method of Example 1, the difference from Example 1 is: In step (1), after adding the template agent tetrapropylammonium hydroxide aqueous solution, the mixture is aged for 24 hours at room temperature to obtain an aged solution. Microwave hydrothermal treatment is not performed. The aged solution is directly mixed with Al2O3. The remaining operations are the same. The ratio of ASA to Al2O3 is adjusted to 0.2:1 (mass ratio) to obtain a catalyst denoted as Pt / Al2O3-ASA, where the mass ratio of ASA to Al2O3 is 0.2:1, that is, the mass of component ASA is 20% of the mass of component Al2O3.
[0052] Comparative Example 3: Prepared according to the method of Comparative Example 1, the difference from Comparative Example 1 is: In step (1), aluminum isopropoxide is not added during the first aging. Instead, tetraethyl orthosilicate (silicon source) and tetrapropylammonium hydroxide aqueous solution (template agent) are directly mixed and aged for 24 hours. The remaining operations are the same. The ratio of the all-silica zeolite precursor S-1-SC to Al2O3 is adjusted to 0.2:1 (mass ratio). The resulting catalyst is denoted as Pt / Al2O3-S-1-SC, where the mass ratio of S-1-SC to Al2O3 is 0.2:1. That is, the mass of component S-1-SC is 20% of the mass of component Al2O3.
[0053] Comparative Example 4: Platinum tetraamminenitrate (platinum loading 0.05%) was directly supported on commercial Al2O3, calcined at 500℃ for 6 h, and further hydrogenated under the condition of reduction at 500℃ for 6 h to obtain the catalyst denoted as Pt / Al2O3.
[0054] Figure 1 The XRD patterns are of the catalysts prepared in Example 1 and Comparative Examples 1-4. Figure 1 It can be seen that the 2θ peak at 20-30° is a broadened and diffuse diffraction peak (enveloping peak) belonging to the zeolite rudimentary crystals, indicating that the synthesized zeolite rudimentary crystals have extremely small grain size and low degree of order. No obvious platinum or its compound diffraction peaks appeared in any of the catalysts, possibly because the Brønsted acid-tunable platinum-based Al₂O₃ / zeolite rudimentary crystals and the amorphous silica-alumina catalyst prepared in this invention have low platinum content and uniform distribution. This indicates that the platinum content used in this scheme is extremely low and platinum does not form other compounds, allowing it to play a hydrogenation role in subsequent reactions, reducing the amount of precious metals used and lowering costs.
[0055] Figure 2 The N2 adsorption and desorption curves of the catalysts prepared in Example 1 and Comparative Examples 1-4 are shown. Figures 3-4 The images show the pore size distribution of the catalysts prepared in Example 1 and Comparative Example 1. Figures 3-4 It can be seen that, based on the data processing results calculated using the BET model for N2 gas adsorption-desorption, Pt / Al2O3-SC-ASA has the largest specific surface area (338 m²).2 / g), which is greater than the specific surface area of Pt / Al2O3-SC (327m²). 2 / g), and much larger than Pt / Al2O3 (226m). 2 According to the pore size distribution diagram, the mesopore size of the zeolite precursor crystals is 4~6 nm (DFT model). This indicates that the addition of zeolite precursor crystals introduces small mesopores (4~6 nm), which increases the specific surface area. Furthermore, the Pt / Al2O3-SC-ASA containing amorphous silicon and aluminum is even larger. This suggests that the addition of zeolite precursor crystals is beneficial to the dispersion of the active phase platinum. The short pores and rich mesopores of the support itself are more conducive to the diffusion of reactants and products, and reduce mass transfer resistance.
[0056] Figures 5-6 The images show TEM images of the catalysts prepared in Examples 1 and Comparative Examples 1-4. As can be seen from the images, the zeolite rudiments are well bonded to Al2O3, and platinum particles are almost not observed. Only a small number of observable platinum particles are observed in the catalysts containing ASA (Pt / Al2O3-SC-ASA and Pt / Al2O3-ASA), indicating that most of the platinum is well dispersed and the particles are small and difficult to observe. This further illustrates that Al2O3 can uniformly disperse platinum metal.
[0057] Figures 7-8 Table 1 shows the NH3-TPD and Py-IR spectra of the catalysts prepared in Examples 1 and Comparative Examples 1-4, and Table 1 shows the acidity of the catalysts prepared in Examples 1 and Comparative Examples 1-4. Figures 7-8 As shown in Table 1, both the total acidity and Brønsted acidity of the catalyst can be adjusted, and Pt / Al2O3-SC-ASA has the best Brønsted acidity.
[0058] Table 1. Acidity of the catalysts prepared in Example 1 and Comparative Examples 1-4 Application Example 1: The hydrocracking experiment was conducted in a 100 mL Laibei high-pressure reactor. First, 0.1715 g naphthalene, 20 mL n-octane, and 50 mg catalyst were added to the reactor, which was then sealed. High-purity hydrogen was introduced to replace the air inside the reactor, maintaining an initial hydrogen partial pressure of 3 MPa. The temperature was increased to 350 °C at a rate of 8 °C / min under conditions of 500 r / min, and then maintained at this temperature for 4 h for hydrosulfurization. Heating was then stopped, and the mixture was cooled to room temperature. After centrifugation, the supernatant was collected and filtered through a 0.22 μm microfilter for GC-FID and analysis of the product content in the liquid.
[0059] The reactant naphthalene was quantitatively analyzed by comparing the retention times of gas chromatography-FID (GC-FID) and standards, and the conversion rate of the reactant was calculated. The conversion rate of naphthalene is calculated as shown in equation (1), and the BTX selectivity is calculated as shown in equation (2), as follows: Equation (1); Equation (2).
[0060] The gas chromatography-flame ionization (GC-FID) instrument was a Shimadzu GC2010plus with a flame ionization detector (FID), and the capillary column was an HP-5 (30m × 0.32mm × 0.25μm). The chromatographic conditions were: split ratio 50, vaporization chamber temperature 280℃, injection volume 1μL. Column oven temperature was increased from 40℃ to 280℃ at a rate of 3℃ / min and held for 5 min. Air flow rate was 200mL / min, hydrogen flow rate was 32mL / min, and make-up flow rate was 24mL / min.
[0061] Application Example 2: The hydrocracking reaction of tetrahydronaphthalene was carried out according to the method of Application Example 1, except that 0.1818 ml of tetrahydronaphthalene, 20 ml of n-octane and 50 mg of catalyst were added.
[0062] Figures 9-10 The graph (con.) shows the conversion and BTX selectivity of the hydrocracking reactions in Examples 1-2. Figures 9-10 It is evident that the Brønsted acid-tunable platinum-based Al2O3 / zeolite precursors and amorphous silica-alumina catalysts prepared in this invention exhibit superior hydrocracking catalytic activity. In the naphthalene hydrocracking reaction, the conversion rates of all four catalysts containing additional acidic components are close to 100%, far exceeding those of the comparative Pt / Al2O3, indicating that the acidic components can promote hydrogenation. Regarding BTX selectivity, Pt / Al2O3-SC-ASA exhibits the highest BTX selectivity, which corresponds to its highest Brønsted acid content. In the tetrahydronaphthalene hydrocracking reaction, the conversion rates show significant changes, with Pt / Al2O3-SC and Pt / Al2O3-S-1-SC showing higher conversion rates than Pt / Al2O3-SC-ASA and Pt / Al2O3-ASA, but Pt / Al2O3-SC-ASA still exhibits the highest BTX selectivity. Overall, Pt / Al₂O₃-SC-ASA achieved optimal metal-acid synergistic control and the best BTX yield, which is also the key product required by this scheme. This indicates that the Brønsted acid-tunable platinum-based Al₂O₃ / zeolite precursor and amorphous silica-alumina catalyst prepared in this invention have superior hydrocracking catalytic activity, and Pt / Al₂O₃-SC-ASA exhibits the best BTX selectivity.
[0063] Example 2: The Brønsted acid-tunable platinum-based Al₂O₃ / zeolite precursors and amorphous silica-alumina catalyst were prepared according to the method of Example 1, the difference being that: The ratio of SC to Al2O3 was adjusted to 0.3:1 (mass ratio), while the ratio of SC to ASA remained at 7:3. The rest of the operation was the same, and the resulting catalyst was denoted as Pt / Al2O3-30%SC-ASA.
[0064] Example 3: The Brønsted acid-tunable platinum-based Al₂O₃ / zeolite precursors and amorphous silica-alumina catalyst were prepared according to the method of Example 1, the difference being that: The ratio of SC to Al2O3 was adjusted to 0.4:1 (mass ratio), while the ratio of SC to ASA remained at 7:3. The rest of the operation was the same, and the resulting catalyst was denoted as Pt / Al2O3-40%SC-ASA.
[0065] Example 4: The Brønsted acid-tunable platinum-based Al₂O₃ / zeolite precursors and amorphous silica-alumina catalyst were prepared according to the method of Example 1, the difference being that: The ratio of SC to Al2O3 was adjusted to 0.5:1 (mass ratio), while the ratio of SC to ASA remained at 7:3. The rest of the operation was the same, and the resulting catalyst was denoted as Pt / Al2O3-50%SC-ASA.
[0066] Preferred Example 1: The Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor catalyst was prepared according to the method of Comparative Example 1. The difference from Comparative Example 1 is that: The ratio of SC to Al2O3 was adjusted to 0.3:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-30%SC.
[0067] Preferred Example 2: The Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor catalyst was prepared according to the method of Comparative Example 1. The difference from Comparative Example 1 is that: The ratio of SC to Al2O3 was adjusted to 0.4:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-40%SC.
[0068] Preferred Example 3: The Brønsted acid-tunable platinum-based Al2O3 / zeolite precursor catalyst was prepared according to the method of Comparative Example 1. The difference from Comparative Example 1 is that: The ratio of SC to Al2O3 was adjusted to 0.5:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-50%SC.
[0069] Preferred Example 4: The Brønsted acid-tunable platinum-based Al2O3 / amorphous silica-alumina catalyst was prepared according to the method of Comparative Example 2. The difference from Comparative Example 2 is that: The ratio of ASA to Al2O3 was adjusted to 0.3:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-30%ASA.
[0070] Preferred Example 5: The Brønsted acid-tunable platinum-based Al2O3 / amorphous silica-alumina catalyst was prepared according to the method of Comparative Example 2. The difference from Comparative Example 2 is that: The ratio of ASA to Al2O3 was adjusted to 0.4:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-40%ASA.
[0071] Preferred Example 6: The Brønsted acid-tunable platinum-based Al2O3 / amorphous silica-alumina catalyst was prepared according to the method of Comparative Example 2. The difference from Comparative Example 2 is that: The ratio of ASA to Al2O3 was adjusted to 0.5:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-50%ASA.
[0072] Preferred Example 7: The Brønsted acid-tunable platinum-based Al2O3 / all-silica zeolite precursor catalyst was prepared according to the method of Comparative Example 3. The difference from Comparative Example 3 is that: The ratio of all-silicon precursor S-1-SC to Al2O3 was adjusted to 0.3:1 (mass ratio), and the rest of the operation was the same, resulting in a catalyst denoted as Pt / Al2O3-30%S-1-SC.
[0073] Preferred Example 8: The Brønsted acid-tunable platinum-based Al2O3 / all-silica zeolite precursor catalyst was prepared according to the method of Comparative Example 3. The difference from Comparative Example 3 is that: The ratio of S-1-SC to Al2O3 was adjusted to 0.4:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-40%S-1-SC.
[0074] Preferred Example 9: The Brønsted acid-tunable platinum-based Al2O3 / all-silica zeolite precursor catalyst was prepared according to the method of Comparative Example 3. The difference from Comparative Example 3 is that: The ratio of S-1-SC to Al2O3 was adjusted to 0.5:1 (mass ratio), and the rest of the operation was the same. The resulting catalyst was denoted as Pt / Al2O3-50%S-1-SC.
[0075] Figures 11-14 This is a comparison chart of the conversion rate and BTX selectivity of the catalysts prepared in Examples 1-4, Comparative Examples 1-3, and Preferred Examples 1-9 in the tetrahydronaphthalene hydrocracking reaction. Figures 11-14It can be seen that for Pt / Al2O3-SC and Pt / Al2O3-S-1-SC catalysts, as the SC loading ratio increases from 20% to 50%, the conversion first increases and then decreases, while the BTX selectivity continues to increase. It is speculated that the Brønsted acid content of the catalyst also gradually increases. Furthermore, the BTX selectivity of Pt / Al2O3-SC is generally higher than that of Pt / Al2O3-S-1-SC, indicating that the acidity of SC is more conducive to the cracking reaction. For Pt / Al2O3-SC-ASA and Pt / Al2O3-ASA catalysts, the conversion also increases first and then decreases, but is generally lower than that of the first two catalysts. This corresponds to the fact that platinum is more likely to migrate and aggregate on ASA, resulting in fewer hydrogenation sites, as observed by TEM. The BTX selectivity decreases significantly when the acid loading is 50%, and the sum of the total selectivity of liquid products is less than 1. This is because of the excess Brønsted acid, which causes the substrate to be excessively cracked into gaseous products. Based on the above analysis, this invention reveals for the first time that in the hydrocracking reaction of tetrahydronaphthalene catalyzed by platinum-based Al2O3 / embryonic-amorphous silica-alumina catalyst, the volcano-shaped conversion curve and the monotonically increasing trend of BTX selectivity are not due to a linear change in the strength of a single acid, but rather a macroscopic manifestation of the interplay between two competing pathways: ring-opening cracking kinetics matching and overload cracking. This invention breaks through the traditional linear thinking that more acid sites in the catalyst lead to higher conversion, precisely defining the optimal operating window for Brønsted acid loading. More importantly, this invention uses a total liquid-phase selectivity of less than 1 as a clear early warning indicator for Brønsted acid overload, providing a novel and reliable criterion for the precise control of metal-acid balance in hydrocracking catalysts, fully demonstrating the technical originality and non-obviousness of this invention.
[0076] The catalysts of Examples 1-4, Comparative Examples 1-3, and Preferred Examples 1-9 were tested with reference to Application Example 1. Figures 11-14 The conversion results of the catalyst in the hydrocracking reaction of tetrahydronaphthalene show that the optimal catalyst is Pt / Al₂O₃-30%SC-ASA, which achieves the best balance between conversion and selectivity. This demonstrates that the synergistic effect of the catalyst's pore structure and acid properties on improving the overall performance of the hydrocracking catalyst.
[0077] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A platinum-based Al₂O₃ / prototype and amorphous silica-alumina catalyst tunable by Brønsted acid, characterized in that, The composite carrier consists of Al2O3, zeolite precursors and amorphous silicon-aluminum, and platinum loaded on the composite carrier.
2. The Brønsted acid-tunable platinum-based Al₂O₃ / proto-crystal and amorphous silica-alumina catalyst according to claim 1, characterized in that, The platinum loading is 0.01~0.1wt%, and the platinum loaded on the composite carrier is uniformly distributed.
3. The Brønsted acid-tunable platinum-based Al₂O₃ / proto-crystal and amorphous silica-alumina catalyst according to claim 1, characterized in that, The zeolite precursor crystals have a particle size of 6-15 nm; the zeolite precursor crystals have stacked mesopores with a pore size of 4-8 nm.
4. A method for preparing a platinum-based Al2O3 / prototype and amorphous silica-alumina catalyst with tunable Brønsted acid as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Mix silicon source and aluminum source, perform first aging, add template agent, perform second aging, and then perform microwave hydrothermal treatment to obtain zeolite crystalline liquid containing amorphous silicon and aluminum. S2. Zeolite precursor containing amorphous silicon and aluminum is impregnated onto Al2O3 to obtain a composite carrier precursor; S3. Prepare a platinum precursor dispersion, and load the prepared platinum precursor dispersion onto the composite support precursor to obtain the catalyst precursor. S4. The catalyst precursor is heat-treated and then reduced to obtain platinum-based Al2O3 / zeolite precursors and amorphous silica-alumina catalysts with tunable Brønsted acid.
5. The method for preparing a Brønsted acid-tunable platinum-based Al₂O₃ / proto-crystal and amorphous silica-alumina catalyst according to claim 4, characterized in that, Step S1 includes one or more of the following: a. The aluminum source includes one or more of aluminum isopropoxide, aluminum nitrate, and aluminum chloride; b. The silicon source includes one or more of tetraethyl orthosilicate, water glass, and silica sol; c. Template agents include tetrapropylammonium hydroxide; d. The actual silicon-to-aluminum ratio of the obtained zeolite rudiments is greater than or equal to 30; e. The molar ratio of silicon to template agent in the silicon source is 1:(0.5~0.8); the first aging time is 8~16h, and the temperature includes room temperature; the second aging time is 20~36h, and the temperature is room temperature; f. The microwave hydrothermal treatment includes sequential low-temperature hydrothermal treatment and high-temperature hydrothermal treatment; The low-temperature hydrothermal treatment is performed at a temperature of 50~100℃ for a time of 70~120min; The high-temperature hydrothermal treatment is performed at a temperature of 120~150℃ for a time of 40~80 minutes.
6. The method for preparing a Brønsted acid-tunable platinum-based Al₂O₃ / prototype and amorphous silica-alumina catalyst according to claim 4, characterized in that, In step S2, the composite carrier precursor is dried to constant weight in air at a temperature of 60~120℃ before proceeding to the next step of processing.
7. The method for preparing a Brønsted acid-tunable platinum-based Al₂O₃ / prototype and amorphous silica-alumina catalyst according to claim 4, characterized in that, The platinum precursor dispersion in step S3 includes a water-soluble platinum salt; the catalyst precursor is dried to constant weight in air at a temperature of 60~120℃ before proceeding to the next step of processing.
8. The method for preparing a Brønsted acid-tunable platinum-based Al₂O₃ / proto-crystal and amorphous silica-alumina catalyst according to claim 4, characterized in that, In step S4, the heat treatment includes calcination, in which the atmosphere is air, the temperature is 300~800℃, and the time is 2~8h; the reduction treatment is in which the atmosphere is hydrogen, the temperature is 200~600℃, and the reduction time is 2~8h.
9. The application of a platinum-based Al₂O₃ / prototype and amorphous silica-alumina catalyst with tunable Brønsted acid as described in any one of claims 1 to 3, characterized in that, Brønsted acid-tunable platinum-based Al2O3 / prototype and amorphous silica-alumina catalysts are used in catalytic hydrocracking processes.
10. The application of the Brønsted acid-tunable platinum-based Al₂O₃ / proto-crystal and amorphous silica-alumina catalyst according to claim 9, characterized in that, Hydrocracking processes include the hydrocracking of polycyclic aromatic hydrocarbons.
Citation Information
Patent Citations
Amorphous silica-alumina containing medium-strong Bronsted acid as well as preparation method and application of amorphous silica-alumina
CN119186544A